The political economy of food price policy in Senegal - Resnick, Danielle (Oxford University Press, 2014)
Since independence, Senegal has been highly reliant on international markets to meet its food needs, this tendency has only increased with rapid levels of urbanization in recent decades. Poor domestic cereal harvests prior to 2007 exacerbated this import-dependence during a time of high global food prices, resulting in the cost of rice sky-rocketing. Government response was to suspend customs duties and value added taxes, providing consumer subsidies and other modes of social protection, and launching a high-profile agricultural initiative. This chapter argues that the policies which emerged reflected the confluence of a strong, diverse civil society placing disparate pressures on a government increasingly centralized around the personality and populist impulses of its former president. Senegal remains vulnerable to future food price crises, learning from these policy mistakes should be a key priority for government.